Predictors of chewing and swallowing disorders after surgery for locally advanced oral cancer with free flap reconstruction: A prospective, observational study. (September 2018) - Ohkoshi, Akira; Ogawa, Takenori; Nakanome, Ayako; Ishida, Eiichi; Ishii, Ryo; Kato, Kengo; Katori, Yukio
Abstract: Objective: Surgery for locally advanced oral cancer often requires wide resections of multiple subsites of the oral cavity, including the oral tongue, floor of the mouth, and lower gingiva, and it causes chewing and swallowing disorders. The aim of this prospective, observational study was to determine which subsites have a greater impact on chewing and swallowing disorders after surgery. Methods: A prospective, observational study was conducted involving 52 patients who underwent surgery for locally advanced oral cancer with free flap reconstruction. The patients' Functional Oral Intake Scale scores were measured before surgery and 1 and 3 months after surgery. Possible predictors of chewing and swallowing disorders were subjected to univariate analysis and multivariate logistic regression analysis. Age, sex, preoperative body mass index, clinical stage, extent of mandibular bone resection, floor of the mouth resection, total or subtotal glossectomy, laryngeal suspension, bilateral neck dissection, and postoperative radiation therapy were the variables evaluated. Results: Multivariate logistic regression analysis showed that both anterior or extensive mandibular bone resection and postoperative radiation therapy were independently associated with poor oral intake after surgery. Conclusions: The identified predictors will be helpful for better management of patients identified as being at high risk of chewing and swallowing disorders. Highlights: Multivariate analysis of chewing and swallowing disorders after oral cancer surgery were conducted. Anterior or extensive mandibular bone resection was a predictor of dysphagia. Postoperative radiation therapy was also a predictor of dysphagia.